5t-12t=

Simple and best practice solution for 5t-12t= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t-12t= equation:


Simplifying
5t + -12t = 0

Combine like terms: 5t + -12t = -7t
-7t = 0

Solving
-7t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Divide each side by '-7'.
t = 0

Simplifying
t = 0

See similar equations:

| x+1overx=6 | | 14x(x-y)+(x-y)=0 | | 6x-2(-6x+7)=130 | | 2(x^2-476)=0 | | 42=-7x | | 510=-10(-8x+5) | | ln(x)=ln(8)-2ln(x) | | 10-49=39 | | 4p-6=18 | | 4x+2(3x+4)=128 | | 5(x+2)-3(x-2)=2x+4 | | -38=-4x+5(4x+18) | | P(7)+P(8)+P(9)+P(10)+P(11)+P(12)+P(13)+P(14)= | | 2h+12=8h-36 | | 5(-6x+13)=275 | | 34-35= | | -9(-6x+8)=468 | | P(2)+P(3)+P(4)+P(5)+P(6)+P(7)+P(8)+P(9)= | | -2x-6(-x-10)=16 | | 3(x-0.8)=(4x+4) | | cos(2x)+3cosx+2=0 | | 5(2-x)+5=10-4x | | cos*2x+3cos*x+2=0 | | 18+2x+0.666x=4 | | 2x+3(4x-14)=112 | | 6x+3x+7.3=5+35.2 | | 4y+x=5(2x-y) | | 6x+4(-4x-14)=-176 | | 5m^2-50m=0 | | 4x+3(-3x+13)=89 | | 7+(-5)=12 | | 0=0.3*4180*(t-20)+0.1*385*(t-400) |

Equations solver categories